DEVELOPMENT AND VALIDATION OF RP-HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF AZILSARTAN MEDOXOMIL AND CHLORTHALIDONE IN BULK AND TABLET DOSAGE FORM - Aher, S. S.; Saudagar, R. B.; Kothari, Hemant (International Journal of Current Pharmaceutical Research, 2018)
Objective: A simple, precise, accurate method was developed for the simultaneous estimation of azilsartan and chlorthalidone in bulk and tablet dosage form by RP-HPLC technique. Methods: Acetonitrile and water in the ratio of (70:30) pH 2.8 used as mobile phase run through (Cosmosil C18 (4.6ID x 250 mm, Particle size: 5 micron) column with a flow rate of 0.9 ml/min. The temperature of the column oven was maintained at 30 °C. Wavelength was selected 244 nm. Stock and working solutions were prepared by using the diluents water and acetonitrile in the ratio of 50:50. Runtime was fixed to 9 min. Results: Chlorthalidone and azilsartan were eluted at 2.02 and 3.92 with good resolution the plate count, tailing factor and all system suitability parameters are within ICH range. Azilsartan Medoxomil and Chlorthalidone were found to be linear low in concentration range of 80-400μg/ ml and 25-125μg/ ml respectively in the linearity study, regression equation and coefficient of correlation for Azilsartan Medoxomil and Chlorthalidone were found to be (y = 28695x+15397 r²=0.995) and (y=13444+27405 r² = 0.996) Percentage recovery for both Azilsartan Medoxomil and Chlorthalidone was found in range of 99.89%-99.96% indicating accuracy of the proposed work. Assay of the tablet was performed and found as 100.15%. Conclusion: All the parameters were within the ICH guidelines, and the method was economical and simple as retention times were less than in literature and decreased run time.